EFFECTIVE ASPECTS OF THE ABRYSVO VACCINE: A BIBLIOGRAPHIC REVIEW - Marques de Souza, Ana Julia; Rocha Cardoso , Talita; Pereira Cirqueira, Tainá (Revista de Patologia do Tocantins, 2025)
Introduction: ABRYSVO (RSVpreF) was developed as a vaccine aimed at combating respiratory syncytial virus in children under 2 years old. It is recommended for pregnant women between 32 and 36 weeks of gestation to prevent lower respiratory tract diseases (LRTD) and severe LRTD caused by respiratory syncytial virus (RSV) in infants from birth to 6 months of age, as well as for individuals aged 60 years and older. In this regard, this study aims to present the main findings about the Abrysvo vaccine through the analysis of available studies on the subject. Methodology: The research was conducted on the platforms "EBSCO" and "LILACS," using the term "Abrysvo." Studies that did not address the ABRYSVO vaccine or that did not provide access to the full text were excluded from the analysis. Relevant information was extracted from each selected article, covering data on the vaccine's efficacy, age groups, adverse effects, and the statistical criteria used. Results and Discussion: The studies show that the efficacy of RSVpreF in infants from birth to 6 months of age met the statistical success criteria for reducing severe lower respiratory tract disease due to respiratory syncytial virus (RSV) at all time points up to 180 days. However, the efficacy verification results did not meet the statistical success criteria for reducing lower respiratory tract disease due to RSV. Furthermore, it was demonstrated that in individuals aged 60 years and older, immunization met the success criteria for the primary objectives of preventing RSV-LRTD with more than two respiratory symptoms and with more than three symptoms. Additionally, it was observed that the most common adverse effect of immunization was pain at the injection site, occurring in 40.6% of vaccinated patients compared to 10.1% of those who received a placebo. Fatigue, headache, muscle pain, and nausea were also noted as possible side effects. Conclusion: The analysis of articles on the efficacy of Abrysvo demonstrates promising results regarding the prevention of severe RSV cases, contributing to the protection of public health expenditures. In summary, although RSVpreF shows significant efficacy, it is crucial that future research continues to monitor and evaluate its performance, ensuring that vaccination strategies are optimized to maximize health benefits for the population.